2023
DOI: 10.1186/s12889-023-15072-5
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial stewardship implementation before and during the COVID-19 pandemic in the acute care settings: a systematic review

Abstract: Introduction Antibiotics are widely administered for various indications, leading to increased antimicrobial resistance (AMR) in acute care hospitals. Since the onset of the COVID-19 pandemic, Antimicrobial Stewardship (AMS) effective strategies should be used to maintain the rational use of antibiotics and decrease the threat of Antimicrobial Resistance (AMR). Aim This systematic literature review aims to investigate the AMS intervention Before-th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…COVID-19 highlighted the effectiveness of antimicrobial stewardship (AMS) in combating AMR by guiding strategic choices during the pandemic and encouraging judicious antibiotic use. Findings from this study showed that amoxicillin/clavulanic acid, classified in the “Access group,” emerged as the most frequently prescribed antibiotic ( Elshenawy et al, 2023 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…COVID-19 highlighted the effectiveness of antimicrobial stewardship (AMS) in combating AMR by guiding strategic choices during the pandemic and encouraging judicious antibiotic use. Findings from this study showed that amoxicillin/clavulanic acid, classified in the “Access group,” emerged as the most frequently prescribed antibiotic ( Elshenawy et al, 2023 ).…”
Section: Discussionmentioning
confidence: 91%
“…Antimicrobial resistance (AMR) constitutes a silent and rapidly escalating pandemic, presenting a critical challenge to global health security ( Salam et al, 2023 ). The introduction of penicillin in the 1920s was a transformative era in the field of infection management, significantly diminishing mortality rates associated with infections ( Elshenawy et al, 2023 ). Despite these advances, the emergence and escalation of AMR, primarily attributed to the inappropriate prescription of antibiotics, casts a long shadow over these achievements.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of documentation indicates poor prescribing practices; ASP should address gaps by deploying evidence-based, multifaceted and stepwise interventions. [ 16 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…This toolkit promotes timely, responsible antibiotic use by initiating effective therapies and then actively reviewing regimens within 24-72 h. The 'Start Smart, Then Focus' principles apply to all antibiotic prescriptions to streamline antimicrobial use. Antimicrobial stewardship encompasses interventions aimed at improving appropriate antibiotic prescribing across all healthcare settings [6,7].…”
Section: Introductionmentioning
confidence: 99%